Ecuador: The Controversy between State and Market. Synthesis from Economic History - Paz y Miño-Cepeda , Juan José (2019)
The old controversy between the State and the market in Ecuador has resurfaced. The idea that prevails today is that a free market and private enterprise should be the engine of the economy and the State must withdraw from this sphere. However, this idea neglects the historical perspective, which demonstrates the necessary action of the State in the economy and, moreover, states that interventionism has been fundamental for the development, modernization and progress of Ecuador. With tacit state policies in favor of society, it has been possible to improve living and working conditions.